2019
DOI: 10.2134/agronj2018.07.0442
|View full text |Cite
|
Sign up to set email alerts
|

Yield, Forage Nutritive Value, and Preference of Legumes under Horse Grazing

Abstract: Alfalfa had better persistence than red or white clover in horse pastures. • Inclusion of grass increased yield of clover pastures but not alfalfa pastures. • Inclusion of grass decreased nutritive values of legume pastures. • On average, legume pastures contained 111 g kg -1 of nonstructural carbohydrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Catalano et al. (2019) reported a change in WC to grass ratio from 5.1:1 in the seeding year to 0.8:1 in the first production year, and Schils et al. (1999) reported that the grazing activity of the dairy cows reduced clover content by 12% compared to the cutting control.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Catalano et al. (2019) reported a change in WC to grass ratio from 5.1:1 in the seeding year to 0.8:1 in the first production year, and Schils et al. (1999) reported that the grazing activity of the dairy cows reduced clover content by 12% compared to the cutting control.…”
Section: Resultsmentioning
confidence: 99%
“…If a horse consumed 2.0% of their bodyweight (BW) on a dry matter (DM) basis each day, the reported equine DE values for all grasses would meet or exceed the horse's needs. Equine DE is not commonly reported for perennial CSG; however, it has been discussed for annual CSG (Grev, Sheaffer, DeBoer, Catalano, & Martinson, 2017), annual warm season grasses (DeBoer et al., 2017), and legumes under horse grazing (Catalano et al., 2019). In other forage species, equine DE ranged from 2.0 to 2.77 Mcal kg −1 (DeBoer et al., 2017; Grev et al., 2017; Catalano et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, there were nine different treatments, including Kentucky bluegrass, Kentucky bluegrass–alfalfa mixture, Kentucky bluegrass–white clover mixture, meadow fescue, meadow fescue–alfalfa mixture, meadow fescue–white clover mixture, orchardgrass, orchardgrass–alfalfa mixture, and orchardgrass–white clover mixture. Plots measured 22 by 12 ft, and seeding rates were 25, 15, 6, 10, and 3 lb per acre, respectively, for meadow fescue, orchardgrass, Kentucky bluegrass, alfalfa, and white clover (Allen et al., 2013; Catalano, Sheaffer, Grev, DeBoer, & Martinson, 2019). Soil pH, potassium (K), and phosphorous (P) were adequate for grass–legume pasture production according to Minnesota fertility guidelines (6.6 pH, 85 ppm K, 18 ppm P) (Kaiser, Lamb, & Eliason, 2011).…”
Section: Experimental Design and Treatmentsmentioning
confidence: 99%
“…When horses grazed perennial cool‐season grasses in monoculture, Kentucky bluegrass and meadow fescue were among the most preferred grasses (>60% removal), whereas orchardgrass was among the least preferred (47% removal) (Allen et al., 2013). Additionally, in research evaluating legumes under horse grazing, horses preferred white and red clover ( Trifolium pratense L.) compared with alfalfa (Catalano et al., 2019). Although research comparing horse preferences of legume–grass mixtures is largely unavailable, legumes resulted in improved palatability among grazing ruminants (Rutter, 2006).…”
Section: Horse Preferencementioning
confidence: 99%